Wide-temperature-range high-performance high-binding-force soft and hard composite coating as well as preparation method and application thereof
Through the preparation of a composite coating with high performance and high binding force, soft and hard, and ion implantation technology is used to form a multi-layer structure, the problem of insufficient mechanical properties of tool coatings at high temperatures is solved, and the wear resistance and impact resistance is significantly improved The corrosion performance extends the service life of the tool.
Patent Information
- Application Number
- CN202411277275.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing tool coatings lack mechanical properties at high temperatures, resulting in severe wear and weak wear resistance and erosion resistance, making it difficult to maintain effectiveness during long-term cutting.
Using a wide temperature domain high performance and high binding force composite coating, the preparation method is adopted to deposit TiZrAlCrSiMN and other hierarchical structures through ion implantation technology to form a dense rutile-type TiO2 structure and amorphous Si3N4, combined with Al2O3 and Cr2O3 protective layers to improve coating The high temperature mechanical properties and oxidation resistance of the layer, and reduce thermal load through the buffering and thermal conductivity of the soft and hard hierarchy.
It significantly improves the high-temperature hardness, wear resistance and erosion resistance of the coating, extends the service life of the tool, reduces the thermal load of the tool edge, enhances the bonding force with the substrate, and avoids early cracking and failure.
Smart Images

Figure CN119121139A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of tool coatings, and in particular to a wide temperature range, high performance, high bonding strength, soft and hard composite coating, and a preparation method and application thereof. Background Art
[0002] Nitrides of transition metals are widely used as reinforcing materials for tool surfaces to improve the surface properties of their substrates due to their high melting point, high hardness, good thermal stability, good corrosion resistance and oxidation resistance. According to the development history of nitride coatings, they can be divided into three generations: the first generation is a single metal nitride coating, such as the well-known TN coating, CrN coating and ZrN coating. Since nitrides of transition metals can be mutually dissolved in the same type, this characteristic can be used to prepare composite nitride coatings, that is, TiN is used as the matrix, and other elements are added to further form an alloy, that is, the second generation of multi-component nitride coatings, such as (Ti,AI)N coating, (Ti,Zr)N coating, (Ti,A1,Zr)N coating and (Ti,Al,Cr)N coating. They successfully improved the thermal hardness and high temperature resistance of the coating by improving the composition of alloying elements.
[0003] In recent years, with the continuous improvement of industrial technology, higher and higher requirements have been put forward for the comprehensive performance of hard coatings, such as hardness, wear resistance, oxidation resistance, erosion resistance, corrosion resistance, crack resistance and bonding strength with the substrate. The results of these improvements depend on the multi-element, multi-structure, nano- and gradient composite of hard coatings, that is, the third generation of nitride coatings. At present, how to improve the preparation process of existing coatings, and then break through the contradiction between strength and toughness, and obtain a hard and soft coating with high hardness and high toughness and good bonding force, is a technical problem that needs to be solved in this field.
[0004] In the Chinese patent with application number 202310681051.4, a bonding layer with good toughness and low hardness is set between the tool substrate and the multi-layer coating to improve the bonding strength of the coating. However, the transition layer is single, the composition difference between the bonding layer and the periodic composite layer is large, there is a difference in thermal expansion coefficient, and the coating is prone to cracking during use and fails prematurely; the thickness of the bonding layer is too thin, although it can improve the bonding strength, it cannot provide a good support for the composite alternating layer and the functional layer, which can easily cause the coating to fail early. The hardness of the coating after high-temperature annealing is a major mechanical parameter of the thermal stability of the coating structure and an important indicator of whether it can be used for a long time. The Al-based coating of this invention has excellent antioxidant properties, but the mechanical properties are insufficient at high temperatures, and it is easy to wear during tool cutting; in the Chinese patent with application number 201680023831.8, the hardness of the embodiment is shown as 2200HV-3200HVG, the hardness is low, and the wear resistance needs to be improved; the purpose of this invention is to improve the anti-adhesion performance during titanium alloy cutting; the coating composition of this invention is mainly Al element , excellent anti-oxidation performance, but insufficient mechanical properties at high temperatures, and easy wear during tool cutting; the embodiment shows that the coating thickness is about 3um, the coating thickness is relatively thin, and the impact resistance needs to be improved; in the coating preparation process, the coating is directly plated after Ar ion etching, and no hardness gradient design is performed, and the bonding strength needs to be improved; in the Chinese patent with application number 202310559774.7, a magnetron sputtering method is used. It can be seen from the attached drawings of the embodiments that the bonding strength (Lc1) between the coating and the substrate is weak, and the partial embodiments before oxidation are less than 5N, and the crack resistance is relatively poor. The hardness of the embodiment is only 28.8GPa, and the wear resistance needs to be improved. The coating thickness is relatively thin, and the embodiment shows that it is only about 1um, and the impact resistance is not strong. During the coating preparation process, three groups of target materials are sputtered at the same time, the process is complicated, and the repetition rate is low. In the Chinese patent with application number 202410258123.9, arc evaporation coating technology is used to prepare the coating. The linear expansion coefficient of the heat-insulating Al2O3 layer and the lubricating CrN layer is significantly different. The surface hardness of the prepared coating is 33-40GPa, which is easy to peel off during service. The surface layer is a lubricating CrN layer. The hardness itself is 1800HV, and the erosion resistance is poor; the task of the hard coating is not only to provide wear protection for the cutting tool substrate, but more importantly to provide thermal protection for the substrate. The common defects in the above four Chinese patents include that during continuous cutting, the tool-chip and tool-workpiece contact areas usually reach high temperatures. The thick coating with low thermal conductivity perpendicular to the tool surface and parallel to the tool surface can provide a thermal barrier for the tool substrate, allowing the generated heat to be transferred to the chips, thereby reducing the thermal load of the tool edge and preventing or delaying the plastic deformation of the tool edge. This was not taken into account during the preparation of the above coatings. Summary of the invention
[0005] The present invention designs and develops a wide temperature range, high performance, high bonding strength, soft and hard composite coating. The purpose of the present invention is to solve the problem that the existing tool coating has weak wear resistance, erosion resistance and crack resistance.
[0006] The present invention designs and develops a method for preparing a wide temperature range, high performance, high adhesion, soft and hard composite coating. The purpose of the present invention is to obtain a wide temperature range, high performance, high adhesion, soft and hard composite coating through coating structure design and process parameter adjustment during the preparation process.
[0007] The present invention designs and develops an application of a wide temperature range, high performance, high bonding strength, soft and hard composite coating, and the purpose of the present invention is to solve the application problem of dry cutting tool coating.
[0008] The technical solution provided by the present invention is:
[0009] A method for preparing a composite coating having high performance and high bonding strength in a wide temperature range and having both softness and hardness, comprising the following steps:
[0010] Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, and then perform ion implantation;
[0011] Step 2: Adjust the argon gas flow to maintain the vacuum state, turn on the Ti target arc power supply to deposit the soft layer of metal Ti, and then turn off the Ti target arc power supply;
[0012] Step 3: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiMN target arc power supply to deposit the hard layer, and then turn off the TiZrAlCrSiMN target arc power supply;
[0013] Step 4: Adjust the argon gas flow to maintain the vacuum state, turn on the Zr target arc power supply to deposit the soft layer metal Zr, and then turn off the Zr target arc power supply;
[0014] Step 5: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiMN target arc power supply to deposit the hard layer, and then turn off the TiZrAlCrSiMN target arc power supply;
[0015] Step 6: Repeat steps 2 to 5 for 3 to 6 cycles and then perform post-processing to obtain the wide temperature range, high performance, high bonding strength, soft and hard composite coating.
[0016] Preferably, in step 1, the cleaning process of the sample to be plated includes: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface.
[0017] Preferably, in step 1, the vacuum is evacuated to 1.3×10 -4Pa ion implantation was performed, and the implanted elements were Zr, Ti and N in turn, the implantation energy was 40keV~120keV, and the implantation dose was 0.5~2×10 17 ions·cm -2 ; Among them, 1×10 17 ions·cm -2 The time is 6h.
[0018] Preferably, in step 1, the Zr ion implantation parameters are: ion beam energy 120keV-80keV, adjustment once every 2 hours, implantation non-uniformity 5%, implantation dose 0.5-2×10 17 ions·cm -2 ;
[0019] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;as well as
[0020] The parameters of N ion implantation are: ion beam energy 120keV~80keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 .
[0021] Preferably, in step 2, the coating speed is set to 2 r / min to 1 r / min, and the furnace temperature is set to 400 to 480°C and the vacuum degree is lower than 5.0×10 -3 After Pa, the coatings are deposited sequentially.
[0022] Preferably, in step 2, the vacuum is maintained at 0.6-1.0 Pa, the current is set to 90-120 A, the bias voltage is -50--350 V, and the duration is 10-20 min;
[0023] In the step 3, the vacuum is maintained at 2.4-3.6 Pa, the partial pressure ratio of nitrogen and argon is 1:2, the current is set to 90-120 A, the bias voltage is -50--100 V, and it lasts for 10-20 min;
[0024] In the step 4, the vacuum is maintained at 0.6-1.0 Pa, the current is set to 130-160 A, the bias voltage is -50--350 V, and the duration is 10-20 min; and
[0025] In the step five, the vacuum is maintained at 2.4 to 3.6 Pa, the partial pressure ratio of nitrogen and argon is 1:2, the current is set to 90 to 120 A, the bias voltage is -50 to -100 V, and it lasts for 10 to 20 minutes.
[0026] Preferably, in step 2, the target material is Ti with a purity of 99.99%;
[0027] In the step 4, the target material is Zr with a purity of 99.99%; and
[0028] In step 3 and step 5, the target material is Ti. a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, a+b+c+d+e+f=1, and the atomic ratio f refers to the total amount of M.
[0029] Preferably, in step six, the post-processing process includes: post-processing the coated sample using mirror sandblasting equipment, the abrasive is an elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6 Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0030] A wide temperature range, high performance, high bonding strength, soft and hard composite coating, prepared by using the method for preparing the wide temperature range, high performance, high bonding strength, soft and hard composite coating, the wide temperature range, high performance, high bonding strength, soft and hard composite coating comprising a deposited soft layer metal Ti, a deposited hard layer, a deposited soft layer metal Zr and a deposited hard layer deposited in sequence;
[0031] The chemical composition and mass percentage of the deposited hard layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, N: 50%; M represents one or more of Hf, Y, and Nb.
[0032] A wide temperature range, high performance, high bonding strength, soft and hard composite coating is applied to dry cutting tools, and the wide temperature range, high performance, high bonding strength, soft and hard composite coating is used.
[0033] The beneficial effects of the present invention are:
[0034] 1. In the composition of the wide temperature range, high performance, high bonding strength, soft and hard composite coating provided by the present invention, the TiZr-based coating, the Zr element at high temperature directly promotes the formation of thermodynamically stable rutile TiO2, and further leads to the formation of a dense TiO2-based structure (when Zr replaces Ti in TiO2 to form (Ti, Zr) O2), increasing the high temperature mechanical properties of the coating (high temperature hardness and high temperature wear resistance); introducing a small radius Si element, the Si element in the coating mainly exists in the amorphous form of Si3N4, making the coating gradually dense and increasing the hardness of the coating; Al and Cr will generate Al2O3 and Cr2O3 protective oxide layers during the oxidation process, which can effectively prevent further diffusion of oxygen into the cemented carbide, ensuring the high oxidation resistance of the coating, and adding Hf, Y, and Nb elements can produce solid solution strengthening to improve the strength and hardness of the coating. The prepared coating has a higher mixing entropy and tends to form a simple solid solution or an amorphous structure, which can meet the strengthening requirements of high entropy alloys and improve wear resistance;
[0035] 2. In the preparation method of the wide temperature range, high performance, high bonding strength, soft and hard composite coating provided by the present invention, the energy-changing ion implantation pre-treatment forms an amorphous strengthening layer. Many studies have shown that surface ion implantation can effectively improve the surface hardness of the material, reduce the friction coefficient and wear, and does not change the surface morphology and roughness of the material. The invention firstly injects large-diameter Zr ions with an injection energy of 80keV to 120keV; then injects small-diameter Ti ions with an injection energy of 40keV to 80keV; and finally injects smaller-diameter N ions with an injection energy of 80keV to 120keV; nuclear collision is mainly used in the Zr ion and Ti injection process, and electron collision is mainly used in the N ion injection process, and precise control of the position distribution of the injected elements is achieved by regulating the injection energy; after ion injection, the surface layer is composed of hard phases such as metal nitrides and nitrogen atom supersaturated solid solutions, with a depth of about 50nm, and the sub-surface layer is mainly composed of metal nitrides. With the increase of the injection dose, the originally isolated damage areas overlap, and finally a long-range disordered amorphous layer is formed, and when subjected to external force, there is no plastic deformation such as grain boundary sliding, and the layer has higher strength and hardness, thereby improving the support effect for the surface coating;
[0036] 3. In the wide temperature range, high performance, high bonding strength and soft-hard composite coating provided by the present invention, the metal soft layer with a certain thickness and hardness accumulated under the hard layer can provide good buffering capacity for the hard layer. When the thickness of the soft layer and the hard layer reaches 1:2, a "synergistic deformation" effect (H 3 / E 2, the anti-plastic deformation factor can roughly measure the wear resistance of the coating. The larger the value, the more likely the coating is to undergo elastic deformation when subjected to load, and the coating is not prone to cracking; the smaller the value, the more likely the coating is to undergo elastic deformation when subjected to load, and the coating is prone to cracking), increasing the service life of the coating under harsh working conditions (improving erosion resistance); the prepared metal soft layer and nitride hard layer are both multilayer structures with a single layer thickness of more than 50nm. The coating material has a low thermal conductivity perpendicular to the tool surface and a high thermal conductivity parallel to the tool surface, which can provide a good thermal barrier for the tool substrate, allowing the generated heat to be transferred to the chips to the maximum extent, thereby reducing the thermal load on the tool edge; from the cross-section of the coating, it can be seen that the interface between the coating and the substrate, and between the soft layer and the hard layer is flat and relatively fuzzy. The invention can achieve good film-base bonding and anti-cracking performance without depositing an adhesive layer;
[0037] 4. In the preparation method of the wide temperature range, high performance, high bonding strength, soft and hard composite coating provided by the present invention, ion implantation technology is used instead of the traditional nitriding method to prepare the transition layer. The implanted modified layer is uniform and stable, and the depth of the modified layer is about 100nm, which avoids the generation of non-ideal nitrides and the problem of uneven nitride generation during the nitriding process; ion implantation can regulate the type of implanted elements and the implantation dose according to the type of coating, coating hardness, and coating elastic modulus. At the same time, ion implantation does not change the dimensional accuracy of the substrate material, effectively improves the transition of the hardness gradient between the substrate and the coating, and significantly improves the bonding strength between the coating and the substrate; ion implantation can be performed at a temperature below 200°C. Compared with nitriding treatment, the processing temperature is lower and the thermal influence on the metallographic structure of the substrate material is smaller;
[0038] 5. The outermost surface of the wide temperature range, high performance, high bonding strength, and soft-hard composite coating provided by the present invention is a nitride phase of TiZrAlCrSiM, which has a high wide temperature range (high and low temperature) surface hardness, erosion resistance and corrosion resistance. It can be seen from the performance results that the soft coating has high plasticity and toughness, but low hardness, poor wear resistance and poor durability; the hard coating has increased hardness and strong wear resistance, but has a high friction coefficient, which is easy to cause brittle fracture, severe wear and adhesion; the soft and hard modulation layer structure design effectively combines the advantages of the two coatings, and can bond the hard layers on both sides of the soft layer with high bonding strength. Under the conditions of drastic temperature changes and impact load application, the elastic deformation of the metal soft layer can eliminate the initiation of coating defects caused by the difference in thermal expansion coefficients between the substrate and the coating, and eliminate the influence of some dynamic loads on the coating life. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the structure of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range according to the present invention;
[0040] Figure 2This is a cross-sectional morphology of a composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range prepared in Example 1 of the present invention;
[0041] Figure 3 This is a cross-sectional morphology of a composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range prepared in Example 2 of the present invention;
[0042] Figure 4 This is a cross-sectional morphology of a composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range prepared in Example 3 of the present invention;
[0043] Figure 5 This is a cross-sectional morphology of a composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range prepared in Example 4 of the present invention;
[0044] Figure 6 This is a comparison chart of the film-base bonding strength of the wide temperature range, high performance, high bonding strength, soft and hard composite coatings prepared in Examples 1 to 4 described in the present invention;
[0045] Figure 7 This is a comparison chart of the nanohardness of the composite coatings with both softness and hardness and high performance over a wide temperature range prepared in Examples 1 to 4 described in the present invention;
[0046] Figure 8 This is a comparison chart of the anti-erosion performance of the wide temperature range, high performance, high bonding strength, soft and hard composite coatings prepared in Examples 1 to 4 of the present invention;
[0047] Fig. 9 It is a schematic diagram of the ion implantation equipment described in the present invention. DETAILED DESCRIPTION
[0048] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0049] like Figure 1 As shown, the present invention provides a wide temperature range, high performance, high bonding strength, soft and hard composite coating, comprising: a soft layer of metal Ti 120, a hard layer of TiZrAlCrSiMN 130, a soft layer of metal Zr 140 and a hard layer of TiZrAlCrSiMN 150 sequentially coated on a substrate 100, and the substrate 100 also includes a base material surface injection layer 110; wherein the soft layer of metal Ti 120, the hard layer of TiZrAlCrSiMN 130, the soft layer of metal Zr 140 and the hard layer of TiZrAlCrSiMN 150 form a 1 modulation periodic layer 200, and after 3 to 6 periodic layers 200 are repeated, a functional layer 300 is formed;
[0050] The chemical compositions and mass percentages of the hard layer TiZrAlCrSiMN 130 and the hard layer TiZrAlCrSiMN 150 are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, N: 50%; M represents one or more of Hf, Y, and Nb.
[0051] like Fig. 9 As shown, the present invention provides an ion implantation device, the implantation method is linear implantation, and the device is mainly composed of an ion system 210, a vacuum system 220, a collection and analysis system, a control system, a water cooling system, a power supply system, an auxiliary system, etc. The prepared sample is placed in a vacuum chamber and fixed on a target table. When the vacuum degree is higher than 1×10 -3 When the pressure is above Pa, start the ion implanter. After the ion source is working, first check the working status of the ion source, and then implant the workpiece. When the set injection amount is reached, turn off the ion source and stop the injection. Compared with conventional ion implantation equipment, this ion implantation equipment can inject gas ions alone, with a maximum injection depth of 500nm from the substrate surface. The injection is carried out at room temperature (water-cooled base), and 1×10 17 ions·cm -2 The time is 6h.
[0052] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0053] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0054] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation was performed after Pa. The implanted elements were Zr, Ti and N, respectively, the implantation energy was 40keV to 120keV, and the implantation dose was 0.5 to 2×10 17 ions·cm -2 ;
[0055] The Zr ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;
[0056] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×1017 ions·cm -2 ;
[0057] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;
[0058] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed of the rotating frame to 2r / min~1r / min, wait until the furnace chamber temperature reaches 400~480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0059] Deposition of soft layer metal Ti 120: adjust the argon flow rate to maintain the vacuum at 0.6-1.0 Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti 120, set the current to 90-120A, bias voltage -50--350V, last for 10-20min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0060] Deposition of hard layer TiZrAlCrSiMN 130: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN 130, set the current to 90-120A, bias voltage -50--100V, last for 10-20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti a Zr b Al c Cr d Si e M f , the formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, a+b+c+d+e+f=1, and the atomic ratio f refers to the total amount of M;
[0061] Deposition of soft layer metal Zr 140: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0 Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr 140, set the current to 130-160A, bias voltage -50--350V, last for 10-20min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0062] Deposition of hard layer TiZrAlCrSiMN 150: Adjust the flow rate of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN 150, set the current to 90-120A, bias voltage -50--100V, last for 10-20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti a Zr b Al c Cr d Si e M f , the formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, a+b+c+d+e+f=1, and the atomic ratio f refers to the total amount of M;
[0063] After repeating the above steps for 3 to 6 cycles, the coating is completed;
[0064] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0065] In another embodiment, in step 2, the Zr ion implantation parameters are: ion beam energy 120keV-80keV (adjusted once every 2h); implantation non-uniformity 5%; implantation dose 1-2×10 17 ions·cm -2 ;
[0066] The parameters of Ti ion implantation are: ion beam energy 80keV~40keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~1×10 17 ions·cm -2 ;
[0067] The N ion implantation parameters are: ion beam energy 120keV~80keV (adjusted every 2h); implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 。
[0068] In another embodiment, in step 3, the rotating speed of the rotating frame is set to 2 r / min to 1 r / min, and the temperature of the furnace chamber is set to 420 to 480°C, and the vacuum degree is lower than 5.0×10 -3After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness in a wide temperature range begins.
[0069] The present invention will be further described below in conjunction with specific embodiments.
[0070] Example 1
[0071] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0072] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0073] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0074] The Zr ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0075] The parameters of Ti ion implantation are: ion beam energy 40 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0076] The N ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0077] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 1r / min, wait until the furnace chamber temperature reaches 420℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0078] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 10min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0079] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0080] Depositing soft layer metal Zr: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 10min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0081] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0082] After repeating the above steps for 4 cycles, the coating is completed;
[0083] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0084] The wide temperature range, high performance, high bonding strength, soft and hard composite coating prepared in this embodiment includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0085] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, and N: 50%.
[0086] Example 2
[0087] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0088] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0089] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0090] The Zr ion implantation parameters are: ion beam energy 80 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1.5×10 17 ions·cm -2 ;
[0091] The N ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0092] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 1.5r / min, wait until the furnace chamber temperature reaches 420℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0093] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 20min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0094] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 10min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Nb 0.02 ;
[0095] Depositing soft layer metal Zr: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 20min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0096] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 10min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Nb 0.02 ;
[0097] After repeating the above steps for 4 cycles, the coating is completed;
[0098] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0099] The wide temperature range, high performance, high bonding strength, soft and hard composite coating prepared in this embodiment includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0100] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Nb: 1%, and N: 50%.
[0101] Example 3
[0102] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0103] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0104] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0105] The parameters of Ti ion implantation are: ion beam energy 80 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 0.5×10 17 ions·cm -2 ;
[0106] The N ion implantation parameters are: ion beam energy 80 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0107] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 1.5r / min, wait until the furnace temperature reaches 450℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0108] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 10min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0109] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Y 0.02 ;
[0110] Depositing soft layer metal Zr: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 20min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0111] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 10min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Y 0.02 ;
[0112] After repeating the above steps for 4 cycles, the coating is completed;
[0113] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0114] The wide temperature range, high performance, high bonding strength, soft and hard composite coating prepared in this embodiment includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0115] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Y: 1%, and N: 50%.
[0116] Example 4
[0117] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0118] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0119] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0120] The Zr ion implantation parameters are: ion beam energy 100 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0121] The parameters of Ti ion implantation are: ion beam energy 60 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0122] The N ion implantation parameters are: ion beam energy 100 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 0.5×10 17 ions·cm -2 ;
[0123] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 2r / min, wait until the furnace chamber temperature reaches 480℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0124] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 20min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0125] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 10min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Hf 0.02 ;
[0126] Depositing soft layer metal Zr: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 10min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0127] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.55 Zr 0.15 Al 0.15 Cr 0.10 Si 0.03 Hf 0.02 ;
[0128] After repeating the above steps for 4 cycles, the coating is completed;
[0129] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0130] The wide temperature range, high performance, high bonding strength, soft and hard composite coating prepared in this embodiment includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0131] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 27.5%, Zr: 7.5%, Al: 7.5%, Cr: 5%, Si: 1.5%, Hf: 1%, and N: 50%.
[0132] Comparative Example 1
[0133] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0134] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0135] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0136] The Zr ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0137] The parameters of Ti ion implantation are: ion beam energy 40 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0138] The N ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0139] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 1r / min, wait until the furnace chamber temperature reaches 420℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0140] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 5min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0141] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0142] Depositing soft layer metal Zr: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 5min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0143] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0144] After repeating the above steps for 4 cycles, the coating is completed;
[0145] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0146] The wide temperature range high performance high bonding strength soft and hard composite coating prepared in this comparative example includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0147] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, and N: 50%.
[0148] Comparative Example 2
[0149] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0150] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0151] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0152] The Zr ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0153] The parameters of Ti ion implantation are: ion beam energy 40 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0154] The N ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0155] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 1r / min, wait until the furnace chamber temperature reaches 420℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0156] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 10min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0157] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 30min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0158] Depositing soft layer metal Zr: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 10min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0159] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 30min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0160] After repeating the above steps for 4 cycles, the coating is completed;
[0161] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0162] The wide temperature range high performance high bonding strength soft and hard composite coating prepared in this comparative example includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0163] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, and N: 50%.
[0164] Comparative Example 3
[0165] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0166] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0167] Step 2: Ion implantation: Place the cleaned sample into the ion implantation vacuum furnace chamber and evacuate to a vacuum degree greater than 1.3×10 -4 Ion implantation after Pa:
[0168] The Zr ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0169] The parameters of Ti ion implantation are: ion beam energy 40 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 1×10 17 ions·cm -2 ;
[0170] The N ion implantation parameters are: ion beam energy 120 keV (adjusted every 2 hours); implantation non-uniformity 5%; implantation dose 2×10 17 ions·cm -2 ;
[0171] Step 3: After the injection is completed, take out the sample and put it into the coating furnace. Set the rotating speed to 1r / min, wait until the furnace chamber temperature reaches 380℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0172] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 10min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0173] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0174] Depositing soft layer metal Zr: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 10min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0175] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0176] After repeating the above steps for 4 cycles, the coating is completed;
[0177] Step 4: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0178] The wide temperature range high performance high bonding strength soft and hard composite coating prepared in this comparative example includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0179] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, and N: 50%.
[0180] Comparative Example 4
[0181] The present invention provides a method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness over a wide temperature range, comprising the following steps:
[0182] Step 1: Cleaning: Immerse the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-dry the surface;
[0183] Step 2: Take out the sample and put it into the coating furnace. Set the rotating speed to 1r / min, wait until the furnace temperature reaches 420℃ and the vacuum degree is less than 5.0×10 -3 After Pa, the deposition of the composite coating with high performance, high bonding strength and both softness and hardness over a wide temperature range begins:
[0184] Depositing soft layer metal Ti: adjust the argon flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Ti target arc power supply to deposit the soft layer metal Ti, set the current to 90-120A, bias voltage -50--350V, last for 10min, turn off the Ti target arc power supply, the target material is Ti target, purity 99.99%;
[0185] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0186] Depositing soft layer metal Zr: adjust the argon gas flow rate to maintain the vacuum at 0.6-1.0Pa, turn on the Zr target arc power supply to deposit the soft layer metal Zr, set the current to 130-160A, bias voltage -50--350V, last for 10min, turn off the Zr target arc power supply, the target material is Zr target, purity 99.99%;
[0187] Deposition of hard layer TiZrAlCrSiMN: Adjust the flow of nitrogen and argon, maintain the vacuum to 2.4-3.6Pa (nitrogen-argon partial pressure ratio is 1:2), turn on the TiZrAlCrSiM target arc power supply to deposit the hard layer TiZrAlCrSiMN, set the current to 90-120A, bias voltage -50-100V, last for 20min, turn off the TiZrAlCrSiM target arc power supply, the target material is Ti 0.40 Zr 0.25 Al 0.20 Cr 0.10 Si 0.03 Y 0.02 ;
[0188] After repeating the above steps for 4 cycles, the coating is completed;
[0189] Step 3: Post-processing of samples: Use mirror sandblasting equipment to post-process the coated samples. The abrasive is elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
[0190] The wide temperature range high performance high bonding strength soft and hard composite coating prepared in this comparative example includes a soft layer of metal Ti, a hard layer of TiZrAlCrSiMN, a soft layer of metal Zr and a hard layer of TiZrAlCrSiMN deposited in sequence to form a modulation cycle, which is repeated for 3 to 6 cycles;
[0191] The chemical composition and mass percentage of the hard layer TiZrAlCrSiMN are: Ti: 20%, Zr: 12.5%, Al: 10%, Cr: 5%, Si: 1.5%, Y: 1%, and N: 50%.
[0192] Test Case
[0193] In the present invention, the following performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 4:
[0194] Nanohardness test: Micro Materials Vantage nanomechanical system, based on the technical specification of JB / T12721-2016 "Solid Material In-situ Nanoindentation Scratch Tester", uses the commonly used diamond tip, 10 points are tested on each sample, and then the average value is taken. The experiment was conducted at room temperature and 500℃, with a maximum load of 50mN, a loading time of 10s, and an unloading time of 10s, to ensure that the indentation depth does not exceed 1 / 10 of the coating thickness.
[0195] Bonding strength: scratch length 3mm, scratch displacement speed 3mm / min, starting load 1N, ending load 200N.
[0196] Erosion resistance: The coating weight loss method is used to characterize the erosion resistance of the coating. The coating is tested according to ASTM-G76. The erosion test conditions are as follows: the sand and dust particle size is less than 125um, the erosion speed is 135m / s, the distance between the nozzle outlet and the test sample surface is about 20mm, and the erosion angle is 45° at level 5 concentration.
[0197] Corrosion resistance: Based on GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", a neutral salt spray test is carried out in a 5% sodium chloride solution environment. The samples are cleaned, weighed, placed, observed, and the salt spray test machine is maintained and adjusted in accordance with the standard. The test cycle is 1440 hours (two months), thereby obtaining the relevant corrosion performance data.
[0198] As shown in Table 1, Table 2, and Table 3, the test results are as follows:
[0199] Table 1 Test results
[0200]
[0201]
[0202] Table 2 Test results
[0203]
[0204] Table 3 Test standards and contact angle test results of Examples 1 to 4
[0205]
[0206] Figure 2 , 3 , 4, and 5 are cross-sectional morphology diagrams of the examples of the present invention. It can be seen that the prepared coating has an obvious multilayer structure, the interface between the layers is clear and flat, no cracks are generated, and it is relatively dense, and the bonding strength with the substrate is more than 78N ( Figure 6 ), which can ensure that there will be no premature cracking during cutting.
[0207] Figure 7 The nano-hardness test results of the embodiments of the present invention are listed. It can be seen that under the same test conditions, the average hardness of the coating exceeds 33Gpa, and the average high-temperature hardness exceeds 29Gpa. Compared with traditional TiN, CrN, AlTiN, AlCrSiN and other coatings, the room temperature hardness is increased by 20%-50%, and the high temperature hardness is increased by 40%-80%. The wide temperature range, high performance, high bonding strength, soft and hard composite coating prepared in the embodiments of the present application has high room temperature and high temperature hardness, and strong high temperature wear resistance. The erosion resistance under the same test conditions is as follows. Figure 8 As shown, compared with the substrate, the erosion resistance of the coating is greatly improved.
[0208] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a composite coating having high performance, high bonding strength, and both softness and hardness in a wide temperature range, characterized in that: The steps include: Step 1: After cleaning the sample to be plated, place it in a coating furnace, evacuate the vacuum, and then perform ion implantation; Step 2: Adjust the argon gas flow to maintain the vacuum state, turn on the Ti target arc power supply to deposit the soft layer of metal Ti, and then turn off the Ti target arc power supply; Step 3: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiMN target arc power supply to deposit the hard layer, and then turn off the TiZrAlCrSiMN target arc power supply; Step 4: Adjust the argon gas flow to maintain the vacuum state, turn on the Zr target arc power supply to deposit the soft layer metal Zr, and then turn off the Zr target arc power supply; Step 5: Adjust the flow of nitrogen and argon to maintain the vacuum state, turn on the TiZrAlCrSiMN target arc power supply to deposit the hard layer, and then turn off the TiZrAlCrSiMN target arc power supply; Step 6: Repeat steps 2 to 5 for 3 to 6 cycles and then perform post-processing to obtain the wide temperature range, high performance, high bonding strength, soft and hard composite coating.
2. The method for preparing a wide temperature range, high performance, high bonding strength, soft and hard composite coating according to claim 1, characterized in that: In the step 1, the cleaning process of the sample to be plated includes: immersing the sample to be plated in acetone, deionized water and anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes respectively, and air-drying the surface.
3. The method for preparing a wide temperature range, high performance, high bonding strength, soft and hard composite coating according to claim 1, characterized in that: In step 1, the vacuum is evacuated to 1.3×10 -4 Pa ion implantation was performed, and the implanted elements were Zr, Ti and N in turn, the implantation energy was 40keV~120keV, and the implantation dose was 0.5~2×10 17 ions·cm -2 ; Among them, 1×10 17 ions·cm -2 The time is 6h.
4. The method for preparing a wide temperature range, high performance, high bonding strength, soft and hard composite coating according to claim 2 or 3, characterized in that: In step 1, the Zr ion implantation parameters are: ion beam energy 120keV-80keV, adjustment every 2 hours, implantation non-uniformity 5%, implantation dose 0.5-2×10 17 ions·cm -2 ; The parameters of Ti ion implantation are: ion beam energy 80keV~40keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 ;as well as The parameters of N ion implantation are: ion beam energy 120keV~80keV, adjusted every 2 hours, implantation non-uniformity 5%; implantation dose 0.5~2×10 17 ions·cm -2 .
5. The method for preparing a composite coating having high performance and high bonding strength over a wide temperature range and both softness and hardness as claimed in claim 4, characterized in that: In step 2, the coating speed is set to 2 r / min to 1 r / min, and the furnace temperature is set to 400 to 480°C and the vacuum is lower than 5.0×10 -3 After Pa, the coatings are deposited sequentially.
6. The method for preparing a wide temperature range, high performance, high bonding strength, soft and hard composite coating according to claim 5, characterized in that: In the step 2, the vacuum is maintained at 0.6-1.0 Pa, the current is set to 90-120 A, the bias voltage is -50--350 V, and the duration is 10-20 min; In the step 3, the vacuum is maintained at 2.4-3.6 Pa, the partial pressure ratio of nitrogen and argon is 1:2, the current is set to 90-120 A, the bias voltage is -50--100 V, and it lasts for 10-20 min; In the step 4, the vacuum is maintained at 0.6-1.0 Pa, the current is set to 130-160 A, the bias voltage is -50--350 V, and the duration is 10-20 min; and In the step five, the vacuum is maintained at 2.4 to 3.6 Pa, the partial pressure ratio of nitrogen and argon is 1:2, the current is set to 90 to 120 A, the bias voltage is -50 to -100 V, and it lasts for 10 to 20 minutes.
7. The method for preparing a wide temperature range, high performance, high bonding strength, soft and hard composite coating according to claim 6, characterized in that: In the step 2, the target material is Ti with a purity of 99.99%; In the step 4, the target material is Zr with a purity of 99.99%; and In step 3 and step 5, the target material is Ti. a Zr b Al c Cr d Si e M f , formula M represents one or more of Hf, Y, and Nb, wherein a, b, c, d, e, and f satisfy 0.40≤a≤0.55, 0.15≤b≤0.25, 0.15≤c≤0.20, d=0.10, e=0.03, f=0.02, a+b+c+d+e+f=1, and the atomic ratio f refers to the total amount of M.
8. The method for preparing a composite coating having a wide temperature range, high performance, high bonding strength and both softness and hardness as claimed in any one of claims 1 to 3 and 5 to 6, characterized in that: In step six, the post-processing process includes: post-processing the coated sample using mirror sandblasting equipment, the abrasive is an elastic soft abrasive doped with diamond micropowder, the sandblasting pressure is 0.3-0.6 Pa, the sandblasting angle is 45°, and the sandblasting time is 30s.
9. A composite coating with high performance, high bonding strength, and both softness and hardness in a wide temperature range, characterized in that: The method for preparing a wide temperature range, high performance, high bonding strength, soft and hard composite coating according to any one of claims 1 to 8 is used, wherein the wide temperature range, high performance, high bonding strength, soft and hard composite coating comprises a deposited soft layer metal Ti, a deposited hard layer, a deposited soft layer metal Zr and a deposited hard layer deposited in sequence; The chemical composition and mass percentage of the deposited hard layer are: Ti: 20% to 27.5%, Zr: 7.5% to 12.5%, Al: 7.5% to 10%, Cr: 5%, Si: 1.5%, M: 1%, N: 50%; M represents one or more of Hf, Y, and Nb.
10. Application of a wide temperature range, high performance, high bonding strength, soft and hard composite coating in dry cutting tools, characterized in that:Use the wide temperature range, high performance, high bonding strength, soft and hard composite coating as described in claim 9.
Citation Information
Cited By
Post-treatment method for CVD (chemical vapor deposition) coating hard alloy cutter
CN120326530A
Cutter sand blasting effect analysis and inspection method and wet sand blasting and elastic sand blasting treatment method
CN120862572A
Wear-resistant hard coating based on TC4 titanium alloy surface ion implantation and ion nitriding as well as preparation method and application of wear-resistant hard coating
CN121023427A
